Temperature and density influence survival in a rapidly declining migratory shorebird. (August 2021) - Cook, Aonghais S.C.P.; Burton, Niall H.K.; Dodd, Stephen G.; Foster, Simon; Pell, Robert J.; Ward, Robin M.; Wright, Lucy J.; Robinson, Robert A.
Abstract: Migratory species face geographically dispersed pressures over the course of their annual cycles. Designing effective conservation strategies for these species requires a detailed understanding of how these different pressures affect demographic rates throughout the annual cycle. As a long-lived species, population trends in the rapidly declining Eurasian curlew Numenius arquata are likely to be highly sensitive to impacts on adult survival. We combine data from multiple sources to analyse survival rates of overlapping populations that breed and/or winter in the United Kingdom . Our analyses demonstrate that curlew survival rates are reduced by cold weather and at high density; however, overall survival rates are high and have increased in recent years. Current population declines are, therefore, likely to be driven by low productivity. As such, efforts to stabilise and reverse declines should focus on increasing breeding success from current estimated levels of 0.25 chicks nest −1 to 0.43 chicks nest −1 . In addition to increasing productivity, effective conservation strategies will need to maintain high levels of survival, which requires an improved understanding of population connectivity and demographic variation throughout the annual cycle.